การลู่เข้าของตัวแบบไตรนามและตัวแบบพหุนามสู่ตัวแบบแบล็ค-โชลส์สำหรับราคาออปชัน - ธนาทร อินทรปัญญา (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Well-known models for computing an option price are the Black-Scholes model and the Binomial model that is divided into n periods. It is known that for large n, the option price from the Binomial model converges to the option price from the Black- Scholes model. In 1986, Boyle presented the Trinomial model for computing an option price and in 2007, Ahn and Song improved the Trinomial model when the movement rates of stock price are based on the model of Cox, Ross and Rubinstein (1979). In this project, we show that the option price computed by the Trinomial model of Ahn and Song converges to the option price from the Black-Scholes model with errors that are less than the Binomial model 2 times. In addition, we use the idea of Ahn and Song to create the Multinomial model that stock price moves in k directions each period and we show that the option price computed by this model converges to the option price from the Black-Scholes model with errors that are less than the Binomial model k− 1 times.